Spatiotemporal dynamics of terrestrial vegetation carbon sinks and its response to climate change in northwest China - Zhang, Xin; Liu, Chenxi; Jiang, Youyan (Frontiers in Environmental Science, 2025)
IntroductionIn the context of global warming, terrestrial ecosystem carbon sequestration is critical for mitigating climate change. However, quantitative estimation of vegetation carbon sinks in arid/semi-arid regions remains a key challenge for understanding global carbon cycling. This study aims to (1) quantify the spatio-temporal dynamics of vegetation carbon sinks in Northwest China (2000–2023) and (2) reveal their responses to climate drivers.MethodsIn this study, by using a multi-source remote sensing dataset of long time series, vegetation Net ecosystem productivity (NEP) in northwestern China (NWC) from 2000 to 2023 was estimated. Based on the NEPs, the spatio-temporal characteristics of vegetation carbon sinks were quantitatively investigated, revealing the spatio-temporal differences in NEP among different underlying surface types. Furthermore, the response relationship between vegetation NEP and climate change was deeply explored by using partial correlation analysis.Results(1) From 2000 to 2023, the Northwest China has served as a carbon sink, with an average carbon sequestration of 217.26 g C·m−2·a−1 and a stable upward trend. Spatially, the regions of carbon sink exhibited a distinct zonal pattern along the China’s dry and wet climate boundary. (2) Over the 24-year period, the dynamic changes in NEP have mainly been characterized by low to moderate fluctuations, NEP in most areas of Northwest China showed an increasing trend, and future NEP is predicted to continue increasing. indicating more stable for NEP. The carbon sequestration capacity differs significantly across different land cover types, but it is increasing about total amount, especially in most areas of the Northwest, and this trend is expected to continue in the future. (3) Climate analysis shows that the temperature and precipitation are generally positively correlated with vegetation carbon sinks, while solar radiation is a negatively correlated with carbon sinks in most areas.DiscussionThe research findings provide important references for vegetation restoration and protection, as well as achieving the goals of “carbon peaking” and “carbon neutrality”. Moreover, it offers scientific insights for studying vegetation carbon sinks in terrestrial ecosystems in mid to high latitude regions globally.